A novel temporal dark-bright solitons conversion system via an add/drop filter for signal security use - Siririth, W.; Mitatha, S.; Pingern, O.; Yupapin, P. P. (My University, 2010)
We propose a new design of a security scheme by using the nonlinear behaviors of temporal dark and bright solitons within a micro-ring resonator system for signal security application. When a dark soliton pulse is input into the proposed system, the chaotic signal is generated, where the required bright soliton pulse can be retrieved and detected by the add/drop filtering device. The chaotic wave form can be cancelled by using an add/drop device, which can be connected and used in the communication link. By using the appropriate ring parameters, simulation results obtained have shown that the soliton conversion can be performed. The ring radii used are within the ranges from 5 to 10 μms and Aeff=0.100.50 μm2. In application, the chaotic signal is generated and formed by the dark soliton within a nonlinear micro-ring device. This can be seen by using the add/drop device, where the bright soliton is formed and detected, which is available to use in communication link. The different temporal soliton response time is seen, the response times of 169 and 84 ns are noted for temporal dark and bright solitons, respectively, which can also be used to form the security key. © 2009 Elsevier GmbH. All rights reserved.
Keywords: Communication security; Dark and bright soliton; Micro-ring resonator; Optical communication